SEMINAR KEAMANAN DAN ETIKA MENGGUNAKAN KOMPUTER UNTUK SISWA SD ISLAM TABANAN - Zaehol Fatah; Resti Aprilianingsih (CV. Denasya Smart Publisher, 2026)
The rapid development of digital technology has changed the interaction and learning patterns of elementary school students in using computers and the internet. This community service activity aims to strengthen the digital literacy of Tabanan Islamic Elementary School students through a seminar on computer security and ethics. This activity provides a great opportunity for Tabanan Islamic Elementary School students to instill an understanding of computer security and ethics. The method used is through several stages, namely planning with the school, conducting an interactive seminar using presentation methods, questions and answers, and simulations of safe internet use, data collection through questionnaires, and activity evaluation. The material presented includes maintaining security and ethics on social media in healthy and responsible computer use. Thus, the seminar on computer security and ethics has been proven to provide benefits in the form of safe and responsible technology use behavior.